Therapeutic Peptides Targeting PPI in Clinical Development: Overview, Mechanism of Action and Perspectives - Cabri, Walter; Cantelmi, Paolo; Corbisiero, Dario; Fantoni, Tommaso; Ferrazzano, Lucia; Martelli, Giulia; Mattellone, Alexia; Tolomelli, Alessandra (Frontiers in Molecular Biosciences, 2021)
Targeting protein-protein interactions (PPIs) has been recently recognized as an emerging therapeutic approach for several diseases. Up today, more than half a million PPI dysregulations have been found to be involved in pathological events. The dynamic nature of these processes and the involvement of large protein surfaces discouraged anyway the scientific community in considering them promising therapeutic targets. More recently peptide drugs received renewed attention since drug discovery has offered a broad range of structural diverse sequences, moving from traditionally endogenous peptides to sequences possessing improved pharmaceutical profiles. About 70 peptides are currently on the marked but several others are in clinical development. In this review we want to report the update on these novel APIs, focusing our attention on the molecules in clinical development, representing the direct consequence of the drug discovery process of the last 10 years. The comprehensive collection will be classified in function of the structural characteristics (native, analogous, heterologous) and on the basis of the therapeutic targets. The mechanism of interference on PPI will also be reported to offer useful information for novel peptide design.